The Influence of Compensation and Work Environment on Employee Job Satisfaction in the Hospitality Industry of Yogyakarta City, Indonesia - Afriliyanti, Tri; Sabaruddin, S. (Golden Ratio of Data in Summary, 2025)
This study examines the effects of compensation and work environment on employee job satisfaction in the hotel industry in Yogyakarta City. The research employed a purposive sampling method, with a sample size of 100 respondents. Primary data were collected through the distribution of questionnaires, which were tested for validity and reliability. The study utilized multiple linear regression analysis, supported by SPSS version 27 software. Statistical tests included validity, reliability, normality, linearity, heteroscedasticity, multicollinearity, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The findings indicate that compensation has a positive and significant effect on employee job satisfaction, as evidenced by a t-value of 5.644 (exceeding the t-table value of 1.661), a positive beta coefficient of 0.352, and a significance level of 0.001 (p < 0.05). Additionally, the work environment demonstrates a positive and significant effect on employee job satisfaction, with a t-value of 9.811 (greater than the t-table value of 1.661), a positive beta coefficient of 0.368, and a significance level of 0.001 (p < 0.05). Furthermore, compensation and work environment simultaneously influence employee job satisfaction significantly, as indicated by an F-value of 117.647 (surpassing the F-table value of 3.09) and a significance level of 0.001 (p < 0.05). Based on the coefficient of determination, the adjusted R² value is 0.702 (70.2%), meaning that compensation and work environment can explain 70.2% of the variation in employee job satisfaction. In comparison, the remaining 29.8% is attributed to factors outside the scope of this study.